2020
DOI: 10.1177/1178636120972695
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Staphylococcus aureus Isolated From Clinical Specimens in a Tertiary Care Hospital, Kathmandu, Nepal

Abstract: Introduction: Methicillin resistant Staphylococcus aureus (MRSA) is a major human pathogen associated with nosocomial and community infections. mecA gene is considered one of the important virulence factors of S. aureus responsible for acquiring resistance against methicillin. The main objective of this study was to explore the prevalence, antibiotic susceptibility pattern, and mec A gene. Methods: A total of 39 isolates of S. aureus were isolated from 954 clinical specimens processed in Microbiology laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 35 publications
3
20
0
Order By: Relevance
“…Similarly, AST of MRSA isolates showed resistance to most of the antibiotics used except carbapenems, vancomycin and gentamicin. Our fi ndings resonate well with some of other fi ndings reported earlier (Thapa et al 2020;Kandel et al 2020;Sah et al 2013;Belbase et al 2017;. However, in another study, ciprofl oxacin was effective against MRSA isolates (Shrestha 2013).…”
Section: Distribution Of Isolates In Different Departments Of the Hossupporting
confidence: 92%
See 3 more Smart Citations
“…Similarly, AST of MRSA isolates showed resistance to most of the antibiotics used except carbapenems, vancomycin and gentamicin. Our fi ndings resonate well with some of other fi ndings reported earlier (Thapa et al 2020;Kandel et al 2020;Sah et al 2013;Belbase et al 2017;. However, in another study, ciprofl oxacin was effective against MRSA isolates (Shrestha 2013).…”
Section: Distribution Of Isolates In Different Departments Of the Hossupporting
confidence: 92%
“…MRSA prevalence in present study is higher than some overseas fi ndings from Iran (5.3%) and Zambia (5.7%) but lower than Ethiopia (12.7%), Libya (19%), Egypt In the antimicrobial susceptibility assay, most of the isolates were susceptible to carbapenems and gentamicin. Higher susceptibility of S. aureus isolates towards these antibiotics was also reported in previous studies (Thapa et al 2020;Kandel et al 2020;Sah et al 2013) and augmented resistance to gentamicin was also reported in another studies (Thulunga et al 2015).…”
Section: Distribution Of Isolates In Different Departments Of the Hossupporting
confidence: 79%
See 2 more Smart Citations
“…49 Globally and in Nepal, the prevalence of MRSA is heterogeneous with varying prevalence (past studies from Nepal: 15.4%-26.0%), 23,50 however, recent studies from Nepal have shown higher prevalence (26%-69%) indicating the rising trend over the years. 51,52 Most of the studies investigating MRSA in Nepal utilized just cefoxitin and oxacillin for screening. Compared to oxacillin, cefoxitin is a better drug to detect mecA gene in MRSA and is considered as a substitute marker.…”
Section: Discussionmentioning
confidence: 99%